¿Y si no en Habana? Landless science, peasant struggle, and capitalist development in Colombia (Alternautas, 2022)
On November 30th 2016, the Colombian government and FARC signed a peace agreement despite its narrow rejection in a national plebiscite two months earlier. The Havana Accords promise to end five decades of civil war. Among the FARC’s central objectives in the negotiations was agrarian reform. This, in order to resolve the highest land inequity in the Western Hemisphere and the accumulated centuries of violent injustice onto the rural poor. About 80% of agricultural land in Colombia is concentrated among 14% of landowners (USAID 2010). Land is most often used for export production and extensive cattle production. From the Andean highlands to the Eastern Plains, cattle dominate the landscape, occupying 80% of agricultural land, often the most productive areas. Another 40% of Colombian territory is under contract with multinational productions for agriculture, forestry, or mining export (OXFAM 2013). Inequality of land access is also borne unequally across race and gender – Afro-Colombians and women facing the highest levels of internal displacement due to rural conflict and agri-business land accumulation (Gomez 2012).